193k views
11 votes
I need help. how do i completely factor 6x^2+7x+2 with an explanation?

1 Answer

5 votes

Answer:

(2x + 1)(3x + 2)

Explanation:

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 6 × 2 = 12 and sum = 7

The factors are + 3 and + 4

Use these factors to split the x- term

= 6x² + 3x + 4x + 2 ( factor the first/second and third/fourth terms )

= 3x(2x + 1) + 2(2x + 1) ← factor out (2x + 1) from each term

= (2x + 1)(3x + 2) ← in factored form

User Austin Berenyi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.